Angiopoietin-1 requires IQ domain GTPase-activating protein 1 to activate Rac1 and promote endothelial barrier defense - David, Sascha; Ghosh, Chandra C; Mukherjee, Aditi; Parikh, Samir M (Arteriosclerosis, thrombosis, and vascular biology, 2011)
IQ domain GTPase-activating protein 1 (IQGAP1) contributes to cytoskeletal network regulation in epithelial cells by its scaffolding properties and by binding the Rho GTPase Rac1 to maintain its activity. The functions of IQGAP1 in endothelial cells beyond angiogenesis remain unclear. We hypothesized that IQGAP1 participates in the regulation of endothelial barrier function. Silencing IQGAP1 in human microvascular endothelial cells resulted in a disruption of adherens junctions, formation of interendothelial gaps, and a reduction in barrier function. Furthermore, silencing of IQGAP1 abrogated the barrier enhancement effect of angiopoietin-1 (Angpt-1) and abolished the barrier-stabilizing effect of Angpt-1 on thrombin-stimulated cells. Coimmunoprecipitation detected binding of endogenous IQGAP1 with Rac1 at baseline that was stronger when Rac1 was activated and weaker when it was deactivated. Measurement of GTP-bound Rac1 revealed that Angpt-1 failed to activate Rac1 not only if IQGAP1 was silenced but also if cells were transfected with a mutant disabled in Rac1 binding (T1050AX2). Furthermore, a dominant-active Rac1 was sufficient to completely reverse the morphological and functional changes induced by reduction in IQGAP1. These experiments are the first demonstration of IQGAP1 regulating barrier function in any cell type. Further, our data show that Angpt-1 requires IQGAP1 as an indispensable activator of Rac1.